Keinginan Menggunakan Metode Kontrasepsi pada Remaja di Masa Mendatang di Provinsi Jawa Timur - Nurul Fajriyah; Nunik Puspitasari (Universitas Airlangga, 2017)
Achievement of Population, Family Planning and Family Development program during the last five years (2007-2012) has stagnated with TFR 2.6. The government change the main focus of family planning on adolescent groups since 2013. The purpose of this study was to analyze the relation of variables with the adolescent’s preference to use contraception method of the future in East Java Province at 2015. This research is an analytic quantitative research with cross-sectional design that consisted of RPJMN year 2015 as secondary data. The sample size are 2,384 adolescents that unmarried and 15–24 years old period January to December 2015 in East Java Province. Independent variables were age, sex, place and education level. The results of this study indicate 56.2% want to use contraception method in the future. After calculated by researcher, it showed that age had p = 0.000, gender had p = 0.000, place had p = 0.003, and education level had p = 0.000. The conclusion of this study is that there are relationship between age, sex, place, and education level with the preference to use contraception method later used chi – square test. BKKBN cooperate with ambassadors of planned generation, and educators should socialization of Family Planning (KB) to motivate young people that plan their families in the future. In addition, need to increase knowledge about reproductive health and family planning for adolescents.